TINJAUAN ASAS-ASAS UMUM PEMERINTAHAN YANG BAIK TERHADAP KEBIJAKAN KARANTINA IMPOR BAHAN BAKUKULIT - Risang Pujiyanto, SH, MPA; Sonny Taufan, SH, MH (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2018)
Leather and Footwear Industry as one of the priority and strategic industries to be developed in Indonesia still encounter problems in the availability of raw materials. The availability of raw materials for leather and footwear industries is minimal in the domestic country causing the industry to import from abroad. The next problem is the raw material must go through the quarantine process by the Agricultural Quarantine Agency, Ministry of Agriculture. This research is an empirical law study. The research material was obtained by field research to obtain primary data and library research to obtain secondary data. Data analysis method used was descriptive qualitative. The results showed that First, the Agricultural Quarantine Agency as one of the government agencies is obliged to apply the Good Principles of Good Governance, which includes the Principle of Utilization, the Principle of Accuracy and the Good Service Principle in the quarantine process of raw material. The write-off of quarantine obligations for the import of finished leather is one of the embodiments of the Utilization Principle. The principle of accuracy is realized by examining the completeness of documents, examination results and test results of raw materials. Second, the application of quarantine that has not been in consistent with service standards has become a note in the application of Good Service Principles. Through the application of Good Governance Principles, it is expected that the availability of raw materials in the leather and footwear industries can begin to be overcome.